(untitled) (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2026)
This study aims to describe the implementation of the demonstration method in Drum Band extracurricular activities at SMK Negeri 4 Kerinci and to identify the supporting and inhibiting factors affecting its implementation. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving the instructor, students, and school representatives. Data was analyzed through data reduction, data display, and conclusion drawing. The findings show that the demonstration method was implemented through planning, instructor demonstrations, student practice, guidance during training, and evaluation of learning outcomes. This method helped students understand drum band playing techniques more effectively because they were able to observe and imitate the instructor directly. Supporting factors included the instructor’s competence, students’ motivation, school support, and adequate facilities and equipment. Inhibiting factors included the limited number of musical instruments, restricted practice time, and differences in students’ abilities to understand the training materials.